Cronología y geografía de una locución prepositiva en español medieval: el caso de menos de - Conde, Juan Carlos (El Colegio de México, 2022)
This article analyses the old Spanish prepositional locution menos de (‘without’) in terms of its diachronic and diatopic implementation, and shows how and why its analysis has been affected by the interference of other prepositional locutions in Old Spanish such as a menos de. It also explores its relations with the Old Catalan and Aragonese locutions menys de (‘without’). The analysis is largely based on data from linguistic corpora. The conclusions of the analysis confirm some recent critical proposals concerning the geographical distribution of certain linguistic phenomena in Old Spanish and the complexity of Old Spanish in terms of its internal variation in the late Middle Ages.